2020
DOI: 10.1039/d0tb00656d
|View full text |Cite
|
Sign up to set email alerts
|

A waterborne polyurethane 3D scaffold containing PLGA with a controllable degradation rate and an anti-inflammatory effect for potential applications in neural tissue repair

Abstract: 3D connected porous LGPU scaffolds with adjustable degradation and a strong anti-inflammatory effect were prepared for neural tissue repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…One purpose of tissue engineering and regenerative medicine is to stimulate the regeneration of damaged tissue and let the body to replace the foreign scaffold with its native cells and secreted ECM. This aim necessitates utilizing biodegradable scaffolds with an appropriate rate of degradation regarding the regeneration rate 55,58 The kinetics of degradation and resorption of scaffold clearly depend on physical properties and mass loss of the scaffold and tissue reconstruction 59,60 In this study, the FCS4 group, which is the most concentrated scaffold, had a slower degradation rate due to a higher degree of cross‐linking than the other groups.…”
Section: Discussionmentioning
confidence: 85%
“…One purpose of tissue engineering and regenerative medicine is to stimulate the regeneration of damaged tissue and let the body to replace the foreign scaffold with its native cells and secreted ECM. This aim necessitates utilizing biodegradable scaffolds with an appropriate rate of degradation regarding the regeneration rate 55,58 The kinetics of degradation and resorption of scaffold clearly depend on physical properties and mass loss of the scaffold and tissue reconstruction 59,60 In this study, the FCS4 group, which is the most concentrated scaffold, had a slower degradation rate due to a higher degree of cross‐linking than the other groups.…”
Section: Discussionmentioning
confidence: 85%
“…Biodegradable thermoplastic PUs can dissolve in organic solvents. This advantage allows the PUs to be processed into scaffolds by applying various techniques, such as particle leaching [ 52 , 87 , 194 , 195 ], thermally induced phase separation (TIPS) [ 49 , 51 , 196 , 197 ], freeze-drying [ 122 , 130 , 131 , 133 , 198 , 199 ], electrospinning [ 31 , [200] , [201] , [202] ], 3D printing [ [203] , [204] , [205] , [206] , [207] ], and their combinations [ 208 , 209 ]. Because of high hydrogen binding, the organic solvents for these biodegradable polyurethanes are polarized solvents, such as dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and hexafluoro-2-propanol (HFIP).…”
Section: Biodegradable Thermoplastic Polyurethane Scaffolds For Tissu...mentioning
confidence: 99%
“…(3) Freeze-drying is not often used for PU scaffold fabrication. The WBPUs in water can be directly freeze-dried and form a porous structure [ 122 , 131 , 133 , 198 , 199 , 210 ]. The pore size can be tuned through altering PU concentration and temperature ( Fig.…”
Section: Biodegradable Thermoplastic Polyurethane Scaffolds For Tissu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of adsorbed proteins on the nanofibers with diameter 950 nm (thick ones) was decreased because of massive conformational changes, while the thin nanofibers (480 nm diameter) maintains the natural shape of proteins and indicated a higher activity rate [ 121 ]. Antibacterial and antifouling properties of PU were reported by several studies [ 122 ]. It has been shown that covalent immobilization of chitosan and citric acid on PU-based materials could develop antibacterial and biocompatibility properties [ 123 ].…”
Section: Pu-protein Interactionsmentioning
confidence: 99%